ASUPAN VITAMIN C DAN E PADA PASIEN JANTUNG KORONER DI RUMAH SAKIT JASA KARTINI KOTA TASIKMALAYA JAWA BARAT - Yanita Listianasari; Salsabila Amanata Nurhaliza (JGK: Jurnal Gizi dan Kesehatan, 2026)
Coronary heart disease (CHD) is a non-communicable disease caused by the narrowing of coronary artery blood vessels, which obstructs blood flow to the heart muscle (atherosclerosis). In Indonesia, the prevalence of coronary heart disease (CHD) reaches 1.5%, in West Java it reaches 1.6%, and in Tasikmalaya, heart disease ranks third among seven non-communicable diseases. The study aims to describe the intake of vitamins C and E in patients with cardiovascular disease at Jasa Kartini Hospital in Tasikmalaya City. The type of research is descriptive quantitative using the purposive sampling method. Data were obtained thru interviews using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) method. The research results show that 55% of respondents have an average vitamin C intake in the good category, whereas 68% of respondents have an average vitamin E intake in the less good category. These results indicate that the majority of patients have met their vitamin C needs, but many have not yet met their vitamin E needs. The low intake of vitamin E is concerning because this vitamin plays a role in preventing LDL oxidation and plaque formation. The conclusion of the study is that the vitamin C intake of most CHD patients is mostly good, but the vitamin E intake is still low.